Copeptin reliably reflects longitudinal right ventricular function. (July 2021) - Harbrücker, Melissa; Natale, Michèle; Kim, Seung-Hyun; Müller, Julian; Ansari, Uzair; Huseynov, Aydin; Zworowsky, Max von; Borggrefe, Martin; Hoffmann, Ursula; Lang, Siegfried; Fatar, Marc; Roth, Thomas; et al.
Background: Data is limited evaluating novel biomarkers in right ventricular dysfunction. Normal right heart function improves the prognosis of patients with heart failure. Therefore, this study investigates the association between the novel biomarker copeptin and right heart function compared to NT-proBNP. Methods: Patients undergoing routine echocardiography were enrolled prospectively. Right ventricular function was assessed by tricuspid annular plane systolic excursion (TAPSE) and further right ventricular and atrial parameters. Exclusion criteria were age under 18 years, left ventricular ejection fraction < 50% and moderate to severe valvular heart disease. Blood samples were taken for biomarker measurements within 72 h of echocardiography. Results: Ninety-one patients were included. Median values of copeptin increased significantly according to decreasing values of TAPSE ( P  = 0.001; right heart function grade I: tricuspid annular plane systolic excursion; TAPSE > 24 mm: 5.20 pmol/L; grade II: TAPSE 18–24 mm: 8.10 pmol/L; grade III: TAPSE < 18 mm: 26.50 pmol/L). Copeptin concentrations were able to discriminate patients with decreased right heart function defined as TAPSE < 18 mm (area under the curves [AUC]: copeptin: 0.793; P  = 0.001; NT-proBNP: 0.805; P  = 0.0001). Within a multivariable linear regression model, copeptin was independently associated with TAPSE (copeptin: T: –4.43; P  = 0.0001; NT-proBNP: T: –1.21; P  = 0.23). Finally, copeptin concentrations were significantly associated with severely reduced right heart function (TAPSE < 18 mm) within a multivariate logistic regression model (copeptin: odds ratio: 0.94; 95% confidence interval: 0.911–0.975; P  = 0.001). Conclusions: This study demonstrates that the novel biomarker copeptin reflects longitudinal right heart function assessed by standardized transthoracic echocardiography compared with NT-proBNP.